Mechanical properties and sulfate resistance of basalt fiber-reinforced alkali-activated fly ash-slag-based coal gangue pervious concrete - Jielian Li; Wenhua Zha; Wenfang Lv; Tao Xu; Bin Wang; Bingwen Wang (Case Studies in Construction Materials)
To address the strength deficiencies and enhance the durability of coal gangue pervious concrete while promoting the resource utilization of coal gangue, this study employs alkali-activated fly ash and slag as binding materials, partially replacing natural coarse aggregates with coal gangue to prepare alkali-activated fly ash-slag-based coal gangue pervious concrete (AFSGPC). Basalt fibers are introduced to examine the effects of varying fiber lengths and volume fractions on the mechanical properties, permeability, and sulfate resistance of AFSGPC. Results indicate that incorporating an appropriate amount of basalt fibers improves the mechanical properties and sulfate resistance of AFSGPC, attributed to the high strength characteristics of the alkali-activated fly ash-slag binder and the crack-bridging and toughening effects of the basalt fibers, although it may slightly reduce permeability. When the fiber length is 12 mm and the volume fraction is 0.1 %, the compressive strength at 28 days reaches 24.12 MPa, and the splitting tensile strength is 2.95 MPa, reflecting increases of 10.48 % and 32.89 %, respectively. The permeability coefficient is measured at 2.07 mm/s, meeting the standards for pervious concrete in road applications. After undergoing 60 cycles of sulfate wet-dry erosion, the corrosion resistance coefficient of AFSGPC increases by 20.02 %. To meet the stringent strength requirements for pervious pavements, it is recommended that basalt fibers with a length of 12 mm and a volume fraction of 0.1 % be utilized in AFSGPC. In regions characterized by high precipitation, the application of basalt fibers shorter than 12 mm, with a volume fraction not exceeding 0.15 %, is advisable to minimize the obstruction of interconnected pores. These findings provide valuable insights for the preparation and engineering application of basalt fiber-modified AFSGPC.